Associations between specific IgE sensitization to 26 respiratory allergen molecules and HLA class II alleles in the EGEA cohort. Issue 8 (7th April 2021) - Gheerbrant, Hubert; Guillien, Alicia; Vernet, Raphaël; Lupinek, Christian; Pison, Christophe; Pin, Isabelle; Demenais, Florence; Nadif, Rachel; Bousquet, Jean; Pickl, Winfried F.; Valenta, Rudolf; Bouzigon, Emmanuelle; et al.
Abstract: Background: Allergy, the most frequent immune disorder affecting 30% of the world's population, is the consequence of immunoglobin E (IgE) sensitization to allergens. Among the genetic factors suspected to be involved in allergy, the HLA class‐II genomic region is a strong candidate. Objective: To assess the association between HLA class‐II alleles and specific IgE (sIgE) sensitization to a large number of respiratory allergen molecules. Methods: The analysis relied on 927 participants of the EGEA cohort, including 497 asthmatics. The study focuses on 26 aeroallergens recognized by sIgE in at least 5% of the study population (determined with the MEDALL chip with sIgE ≥ 0.3 ISU) and 23 imputed HLA class‐II alleles. For each sIgE sensitization and HLA class‐II allele, we fitted a logistic regression model accounting for familial dependence and adjusted for gender, age, and genetic principal components. p ‐values were corrected for multiple comparisons (False Discovery Rate). Results: Most of the 19 statistically significant associations observed regard pollen allergens (mugwort Art v 1, olive tree Ole e 1, timothy grass Phl p 2, Phl p 5 and plantain Pla l 1), three were mold allergen ( Alternaria Alt a 1), and a single one regards house dust mite allergen (Der p 7). No association was observed with pet allergens. The strongest associations were found with mugwort Art v 1 (OR = 5.42 (95%CI, 3.30; 8.88), 4.14 (2.65; 6.47), 3.16 (1.88; 5.31) with DQB1*05:01, DQA1*01:01 and DRB1*01:01, respectively). Conclusion: Our results support the important role of HLA class‐II alleles as immune response genes predisposing their carriers for sensitization to various major pollen allergens. Abstract : This association study between HLA class‐II alleles and specific IgE sensitization to a large panel of aeroallergens reveals 19 statistically significant associations, almost exclusively with pollen allergens. The strongest associations are found for mugwort Art v1, with DQB1*05:01, DQA1*01:01 and DRB1*01:01 alleles. HLA class‐II alleles might be specifically associated with sensitization to seasonal allergens. Abbreviations: IgE, immunoglobin E; HLA, human leukocyte antigen.